The miracle of morphogenesis, cell adhesion, polarity and cytoskeletal regulation - Peifer, Mark (Henry Stewart Talks, 2008)
Self-assembly of cells into tissues and organs, Understanding this process from the molecular to whole animal level, Different cell types, Cell adhesion, Epithelial sheets, Drosophila cell adhesion, Gastrulation, Cadherin expression, Normal cell behavior and human disease, Abelson tyrosine kinase, Ena and Abl, How does Abl function during more complex events of morphogenesis, Other actin regulators, Dorsal closure, Cells use 'landmarks' to establish and elaborate polarity, Adherens junctions, Drosophila cellularization, Bazooka
Reviewed at 2018/05/31